2016
DOI: 10.1002/ejoc.201601236
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Large Polycyclic Aromatic Hydrocarbons with Planar and Non‐Planar Structural Motifs

Abstract: Implementation of non‐planar aromatic motifs in the molecular design of π‐conjugated materials represents a paradigm shift that is interesting from a fundamental research viewpoint but remains largely underdeveloped. To further facilitate this cause, we report on the synthesis and properties of two large polycyclic aromatic compounds (38 carbon atoms). In one compound the planar π‐system pyrene is linked to bowl‐shaped hydrocarbon corannulene through a C=C bond, which is referred to as “corannulene–vinylpyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…Indeed, DR spectroscopic analysis revealed that corannulene integration resulted in appearance of an additional absorption band (550-650 nm) leading to ab athochromic shift of the absorption profile of over 100 nm in comparison with both the pristine COF and corannulene units.S uch ad rastic change could be attributed to charge transfer (CT) between the covalent organic host and pBmoieties,especially taking into account the electron donating character of the framework functional groups (for example,-OMe) and electron-accepting behavior of corannulene moieties. [22] This fact is in line with the results observed in the case of naphthalene (C 10 H 8 ) and pyrene (C 16 H 10 )integration, both possessing higher-lying LUMOs than that of pB-C 20 H 10 (À2.27 eV in contrast to À1.20 eV (C 10 H 8 ) [28] and À1.48 eV (C 16 H 10 ) [29] ), which did not result in CT band formation. Integration of 1,4-dimethoxybenzene and 1,5-dimethoxynaphthalene exhibiting electrondonating behavior also did not result in CT band formation.…”
Section: Angewandte Chemiesupporting
confidence: 86%
“…Indeed, DR spectroscopic analysis revealed that corannulene integration resulted in appearance of an additional absorption band (550-650 nm) leading to ab athochromic shift of the absorption profile of over 100 nm in comparison with both the pristine COF and corannulene units.S uch ad rastic change could be attributed to charge transfer (CT) between the covalent organic host and pBmoieties,especially taking into account the electron donating character of the framework functional groups (for example,-OMe) and electron-accepting behavior of corannulene moieties. [22] This fact is in line with the results observed in the case of naphthalene (C 10 H 8 ) and pyrene (C 16 H 10 )integration, both possessing higher-lying LUMOs than that of pB-C 20 H 10 (À2.27 eV in contrast to À1.20 eV (C 10 H 8 ) [28] and À1.48 eV (C 16 H 10 ) [29] ), which did not result in CT band formation. Integration of 1,4-dimethoxybenzene and 1,5-dimethoxynaphthalene exhibiting electrondonating behavior also did not result in CT band formation.…”
Section: Angewandte Chemiesupporting
confidence: 86%
“…Such a drastic change could be attributed to charge transfer (CT) between the covalent organic host and πB moieties, especially taking into account the electron donating character of the framework functional groups (for example, ‐OMe) and electron‐accepting behavior of corannulene moieties . This fact is in line with the results observed in the case of naphthalene (C 10 H 8 ) and pyrene (C 16 H 10 ) integration, both possessing higher‐lying LUMOs than that of πB‐C 20 H 10 (−2.27 eV in contrast to −1.20 eV (C 10 H 8 ) and −1.48 eV (C 16 H 10 )), which did not result in CT band formation. Integration of 1,4‐dimethoxybenzene and 1,5‐dimethoxynaphthalene exhibiting electron‐donating behavior also did not result in CT band formation.…”
Section: Methodssupporting
confidence: 76%
“…These methods are much less useful for the synthesis of larger planar systems. Therefore, we focused on photochemical cyclization methods, such as the Mallory reaction, , which are widely used in preparation of closed-shell polycyclic aromatic systems, , including helicenes, nanographenes, photoswitches, photochromic materials, , and π-extended corannulenes. …”
mentioning
confidence: 99%